2020
DOI: 10.21608/ejh.2020.22181.1230
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Fasting Attenuates Apoptosis, Modulates Autophagy and Preserve Telocytes in Doxorubicin Induced Cardiotoxicity in Albino Rats: A Histological Study

Abstract: Background: Doxorubicin (DOX) is an effective anticancer drug, however its use is limited due to severe cardiotoxic effects as ventricular dysfunction, cardiomyopathy and heart failure. Intermittent fasting (IF) has a potential preventive and therapeutic effects against variety of diseases including cardiovascular and neurodegenerative disorders. Aim of Work:Investigating the effects of DOX on the histological structure of myocardium and evaluating the possible cardioprotective effects of IF on these changes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…For example, ER has been reported to have a protective effect against kidney damage, the mechanism of which includes exerting anti-apoptotic effects through improving oxidative conditions [ 18 , 41 ]. Similar anti-apoptotic reports exist for TR [ 42 44 ] and IF [ 8 , 45 ]. On the contrary, several studies have shown that the HF diet can induce apoptosis in the kidney and cause further damage during AKI [ 46 48 ].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…For example, ER has been reported to have a protective effect against kidney damage, the mechanism of which includes exerting anti-apoptotic effects through improving oxidative conditions [ 18 , 41 ]. Similar anti-apoptotic reports exist for TR [ 42 44 ] and IF [ 8 , 45 ]. On the contrary, several studies have shown that the HF diet can induce apoptosis in the kidney and cause further damage during AKI [ 46 48 ].…”
Section: Introductionsupporting
confidence: 79%
“…Regarding the effects of diets other than ER, it has been reported that the IF diet has a neuroprotective effect on acute spinal cord injury by reducing the Bax/Bcl-2 ratio [ 45 ]. The TR diet has been shown to have protective effects on the heart by attenuating apoptosis, regulating the autophagy process, and preserving cells [ 42 ]. Another study found that preoperative fasting was protective against renal IRI (ischemic reperfusion injury) by inhibiting apoptosis [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings of the current work have confirmed the mechanistic insights behind the Dox‐induced cardiotoxicity which could be attributed to the disturbed oxidants (MDA)/antioxidants (SOD, Catalase, GSH, GPX, NRF2, and NO) balance noticed in our study. This disturbance leads to highly toxic free radicals being produced, which in‐turn leads to depletion of the endogenous antioxidants and induction of lipid peroxidation and protein oxidation (Abas & Sabry, 2020; Wenningmann et al, 2019). The efficiency of mitochondrial respiration further declines by Dox's induction of hot spot areas in the mitochondrial DNA, which leads to aberrant replication and upsurge in the concentration of reactive oxygen species (ROS) (Lebrecht et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings align with previous research illustrating the anti-apoptotic properties of TRF in diverse animal models. Specifically, TRF has been documented to diminish apoptosis in a mouse model of hepatic IRI [ 31 ] and to mitigate apoptosis through the modulation of autophagy in a doxorubicin-induced cardiotoxicity model of albino rats [ 32 ]. In the context of kidney disease, preoperative TRF administration demonstrated protective effects against renal IRI by inhibiting apoptosis in a mouse model of aortic aneurysm [ 33 ].…”
Section: Discussionmentioning
confidence: 99%